The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s40594-018-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perception of STEM integration and education: a systematic literature review

Abstract: Background: For schools to include quality STEM education, it is important to understand teachers' beliefs and perceptions related to STEM talent development. Teachers, as important persons within a student's talent development, hold prior views and experiences that will influence their STEM instruction. This study attempts to understand what is known about teachers' perceptions of STEM education by examining existing literature. Results: Study inclusion criteria consisted of empirical articles, which aligned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
387
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(569 citation statements)
references
References 31 publications
22
387
0
24
Order By: Relevance
“…A search for reviews of STEM education research found multiple reviews that could suggest approaches for identifying publications (e.g., Brown, 2012;Henderson, Beach, & Finkelstein, 2011;Kim, Sinatra, & Seyranian, 2018;Margot & Kettler, 2019;Minichiello, Hood, & Harkness, 2018;Mizell & Brown, 2016;Thibaut et al, 2018;Wu & Rau, 2019). The review conducted by Brown (2012) examined the research base of STEM education.…”
Section: Guidance From Prior Reviews Related To Stem Educationmentioning
confidence: 99%
“…A search for reviews of STEM education research found multiple reviews that could suggest approaches for identifying publications (e.g., Brown, 2012;Henderson, Beach, & Finkelstein, 2011;Kim, Sinatra, & Seyranian, 2018;Margot & Kettler, 2019;Minichiello, Hood, & Harkness, 2018;Mizell & Brown, 2016;Thibaut et al, 2018;Wu & Rau, 2019). The review conducted by Brown (2012) examined the research base of STEM education.…”
Section: Guidance From Prior Reviews Related To Stem Educationmentioning
confidence: 99%
“…Mathematics teachers feel it is more challenging than science teachers in STEM teaching to help students to solve authentic problems [15]. Researchers [18] analyzed teachers' difficulties in teachers' perceptions of STEM education, including pedagogical and curriculum challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Tang & Williams, 2018). Therefore, a great challenge for teachers in STEM subjects is to design classroom activities that integrate two or more of the subjects in their teaching in both a meaningful and relevant way (Bell, 2016;de Vries, 2017;Kertil & Gurel, 2016;Margot & Kettler, 2019;Radloff & Guzey, 2016). In short, STEM teaching needs to be authentic (cf.…”
Section: Introduction and Aimmentioning
confidence: 99%